1999
DOI: 10.1046/j.1523-1755.1999.07130.x
|View full text |Cite
|
Sign up to set email alerts
|

Low density lipoprotein apheresis therapy for steroid-resistant nephrotic syndrome

Abstract: Low density lipoprotein apheresis therapy for steroid-resistantFocal and segmental glomerulosclerosis (FGS) is a nephrotic syndrome.disease manifesting severe nephrotic syndrome (NS) that Background. The pathogenic role of hyperlipidemia in longthe latter months of 1989 we performed a random protocol LDL-A therapy that included nine episodes of steroid-resistant NS in eight patients who had been diag-Key words: thromboxane B 2 , progressive renal disease, tubulointerstinosed with FGS or MCNS [6]. For the multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 9 publications
2
39
0
Order By: Relevance
“…However, some clinical studies in adults show benefits of LDL apheresis in inducing remission of steroid-resistant nephrotic syndrome [142][143][144][145]. In children, a clinical study involving 11 patients with refractory steroid-resistant nephrotic syndrome reported a (complete or partial) remission rate of 63 %, suggesting that LDL apheresis can help induce remission of refractory steroid-resistant nephrotic syndrome in children [146].…”
Section: Ldl Apheresis and Plasmapheresismentioning
confidence: 99%
See 2 more Smart Citations
“…However, some clinical studies in adults show benefits of LDL apheresis in inducing remission of steroid-resistant nephrotic syndrome [142][143][144][145]. In children, a clinical study involving 11 patients with refractory steroid-resistant nephrotic syndrome reported a (complete or partial) remission rate of 63 %, suggesting that LDL apheresis can help induce remission of refractory steroid-resistant nephrotic syndrome in children [146].…”
Section: Ldl Apheresis and Plasmapheresismentioning
confidence: 99%
“…Specific mechanism(s) behind the beneficial effects of LDL apheresis on this disease remain unclear, but it has been suggested to go beyond the improvement of dyslipidemia. Some reports indicate that LDL apheresis can improve the responsiveness to steroids [143,144,146,147] and cyclosporine [148], and thus combination therapy of LDL apheresis with these drugs is recommended rather than LDL apheresis alone. Efficacy of LDL apheresis has been described to be associated with highly-selective proteinuria (one study showed that patients with complete remission after LDL apheresis had a lower selectivity index [SI], which is calculated as [urinary immunoglobulin G (IgG)/serum IgG] 9 [serum transferrin (Tf)/urinary Tf], of 0.05 ± 0.02, compared with 0.25 ± 0.04 in patients who did not respond to LDL apheresis [146]) or minor renal tubular interstitial damage [146], and thus early LDL apheresis after the onset of the disease is considered advisable [142,146].…”
Section: Ldl Apheresis and Plasmapheresismentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the treatment of nephrotic dyslipidemia with the application of LDL-apheresis [80, 81] or with the use of medications such as statins [82] and direct ACAT inhibitors [83] has a favorable effect on some NS-related parameters such as hypoalbuminemia and albuminuria. These observations clearly demonstrate the existence of a vicious circle involving proteinuria and dyslipidemia.…”
Section: Lipids In Nephrotic Syndromementioning
confidence: 99%
“…LDL-apheresis might absorb glomerular permeability factors (e.g. TNF-, IFN-) in addition to LDL and help decrease proteinuria in patients with steroid-resistant nephrotic syndrome (10). Our patient also underwent therapy with LDL-apheresis, but nephrotic syndrome did not go into remission during the short term.…”
Section: Discussionmentioning
confidence: 70%